Forensic isoscapes based on intra-individual temporal variation of δ18O and 206Pb/207Pb in human teeth - Laura A. Regan; Nathan W. Bower; Samuel J. Brown; Craig C. Lundstrom; Gideon Bartov; Matthew D. Cooney (Forensic Sciences Research, 2021)
Isotopic signatures used in the georeferencing of human remains are largely fixed by spatially distinct geologic and environmental processes. However, location-dependent temporal changes in these isotope ratios should also be considered when determining an individual’s provenance and/or trajectory. Distributions of the relevant isotopes can be impacted by predictable external factors such as climate change, delocalisation of food and water sources and changes in sources and uses of metals. Using Multi-Collector Inductively-Coupled Plasma Mass Spectrometer (MC-ICP-MS) analyses of 206Pb/207Pb in tooth enamel and dentin from a population of 21 ± 1-year-old individuals born circa 1984 and isotope ratio mass spectrometry (IRMS) of δ18O in their enamel, we examined the expected influence of some of these factors. The resulting adjustments to the geographic distribution of isotope ratios (isoscapes) found in tooth enamel and dentin may contain additional useful information for forensic identification, but the shifts in values can also impact the uncertainty and usefulness of identifications if they are not taken into account.KEY POINTS Isoscapes of 206Pb/207Pb and δ18O used for geolocation are not static. Within a few years, the enamel and dentin of a person may exhibit measurable differences in 206Pb/207Pb even without changing locations. Changes in climatic patterns tied to rising temperatures are more significant than the direct effect of increasing temperature on δ18O fixed in tooth bioapatite. Third molar (M3) enamel mineralisation includes material incorporated from before formal amelogenesis takes place.